The PSI–PSII Megacomplex in Green Plants. (11th February 2019) - Yokono, Makio; Takabayashi, Atsushi; Kishimoto, Junko; Fujita, Tomomichi; Iwai, Masakazu; Murakami, Akio; Akimoto, Seiji; Tanaka, Ayumi
Abstract: Energy dissipation is crucial for land and shallow-water plants exposed to direct sunlight. Almost all green plants dissipate excess excitation energy to protect the photosystem reaction centers, photosystem II (PSII) and photosystem I (PSI), and continue to grow under strong light. In our previous work, we reported that about half of the photosystem reaction centers form a PSI–PSII megacomplex in Arabidopsis thaliana, and that the excess energy was transferred from PSII to PSI fast. However, the physiological function and structure of the megacomplex remained unclear. Here, we suggest that high-light adaptable sun-plants accumulate the PSI–PSII megacomplex more than shade-plants. In addition, PSI of sun-plants has a deep trap to receive excitation energy, which is low-energy chlorophylls showing fluorescence maxima longer than 730 nm. This deep trap may increase the high-light tolerance of PSI by improving excitation energy dissipation. Electron micrographs suggest that one PSII dimer is directly sandwiched between two PSIs with 2-fold rotational symmetry in the basic form of the PSI–PSII megacomplex in green plants. This structure should enable fast energy transfer from PSII to PSI and allow energy in PSII to be dissipated via the deep trap in PSI.